PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BADAN NARKOTIKA NASIONAL (BNN) KOTA PALU - Maswita, Maswita (Katalogis, 2017)
The research intends to determine simultaneous and partial influence of leadership styles that include authoritarian, paternalistic, laissez faire, democratic, and charismatic on the performance of officials in The National Narcotics Agency in Palu. Type of research is causal descriptive. Population includes 40 civil servants in The National Narcotics Agency in Palu. Data collection methods are questionnaire, documentation, interviews, and observation. Sample was selected by census method. Type of data is qualitative and quantitative taken from primary and secondary sources. Method of analysis is multiple linear regressions analysis. The result proves that leadership styles that include authoritarian, paternalistic, laissez faire, democratic and charismatic simultaneously and partially have positive and significant influence on the performance of officials ini The National Narcotics Agency in Palu.